2010
DOI: 10.1007/s12011-010-8877-9
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein as Potential Biomarker of Cadmium Exposure in Persian Sturgeon (Acipenser persicus)

Abstract: Metallothionein (MT) concentration in gills, liver, and kidney tissues of Persian sturgeon (Acipenser persicus) were determined following exposure to sublethal levels of waterborne cadmium (Cd) (50, 400, and 1,000 μg l(-1)) after 1, 2, 4, and 14 days. The increases of MT from background levels were 4.6-, 3-, and 2.8-fold for kidney, liver, and gills, respectively. The results showed that MT level change in the kidney is time and concentration dependent. Also, cortisol measurement revealed elevation at the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…The current study revealed that the lowest expression of 0.48-fold (compared to S1) was found in S4, which turned out to be the highest hepatic Cd level site. This is in agreement with the findings of Shariati et al (2011) who found that the Cd levels in the liver of Persian sturgeon increased as the Cd concentration and time exposure increased; however, MT protein level increased only in short period (4 days) after being exposed to Cd, and there was no significant change of MT protein level between 4-and 14-day treatment groups. The accumulations of Cd in the liver might exceed its regulation capacity, leading to disruption in the induction of MT synthesis and eventually loss of the correlation between MT and Cd levels as found at lower exposed concentrations (Shariati et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study revealed that the lowest expression of 0.48-fold (compared to S1) was found in S4, which turned out to be the highest hepatic Cd level site. This is in agreement with the findings of Shariati et al (2011) who found that the Cd levels in the liver of Persian sturgeon increased as the Cd concentration and time exposure increased; however, MT protein level increased only in short period (4 days) after being exposed to Cd, and there was no significant change of MT protein level between 4-and 14-day treatment groups. The accumulations of Cd in the liver might exceed its regulation capacity, leading to disruption in the induction of MT synthesis and eventually loss of the correlation between MT and Cd levels as found at lower exposed concentrations (Shariati et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the findings of Shariati et al (2011) who found that the Cd levels in the liver of Persian sturgeon increased as the Cd concentration and time exposure increased; however, MT protein level increased only in short period (4 days) after being exposed to Cd, and there was no significant change of MT protein level between 4-and 14-day treatment groups. The accumulations of Cd in the liver might exceed its regulation capacity, leading to disruption in the induction of MT synthesis and eventually loss of the correlation between MT and Cd levels as found at lower exposed concentrations (Shariati et al, 2011). When the metal level has surpassed the capability of an animal to produce MT, the metal may bind to high molecular mass proteins, but with a weaker affinity than the Cd toxicity may follow (De Boeck et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the studies conducted in MT transgenic mice or MT-null mice models provide strong evidence that MTs play an essential role in protecting cells from acute heavy metal poisoning (15)(16)(17)(18). It is evident that MTs can be a useful biomarker for the prediction of heavy metal toxicity and adverse biological outcome (19,20).…”
Section: Induction Of Metallothionein (Mt) Expression Is Involved In mentioning
confidence: 99%
“…In previous studies, the 48-h exposure to Cd concentrations of 50 and 367 μg/L induced mRNA expression of MT in Persian sturgeon (Acipenser persicus) and Korean spotted barbell (Hemibarbus mylodon), respectively (Cho et al 2008;Shariati et al 2011). For yellow catfish (P. fulvidraco), significant enhancement of hepatic MT transcription was reported at 6 h of exposure to 5 mg/L Cd (Kim et al 2012).…”
Section: Phylogenetic Analysismentioning
confidence: 90%